Non-invasive detection of bladder cancer by identification of abnormal CD44 proteins in exfoliated cancer cells in urine. Issue 3 (June 1995) - Sugiyama, M; Woodman, A; Sugino, T; Crowley, S; Ho, K; Smith, J; Matsumura, Y; Tarin, D
Abstract : Aims —To investigate the expression of CD44 proteins in exfoliated urothelial cells and in tumour tissues from bladder cancer patients. A further objective was to evaluate the diagnostic potential of the changes observed in the expression of these proteins as a marker for non-invasive detection of bladder cancer. Methods —Naturally voided urine specimens were collected from 47 patients with bladder cancer or severe urothelial dysplasia (n=3) and from a control group of 43 people with no evidence of neoplastic disease. Exfoliated urothelial cells floating in the urine were pelleted by centrifugation and lysed, and their constituent proteins extracted. The pattern of expression of CD44 proteins in each sample was examined by western blot analysis using a monoclonal antibody, Hermes 3, which recognises an epitope on the polypeptide backbone of the CD44 protein. Immunohistochemical studies were performed on neoplastic (n=10) and normal (n=4) bladder tissue specimens which were snap frozen in liquid nitrogen before examination with antibodies to CD44 gene products (CD44s and CD44v6). Results —Western blot analysis revealed several high molecular weight CD44 isoforms > 160 kDa in urine cell lysates from 75% of patients with histologically confirmed bladder cancer and in two of the three patients with severe dysplasia. Such patterns were not detected in the urine cell pellets from any persons in the control group. Immunohistochemical studies of the tissue distribution of CD44s and CD44v6 showed that the differentiation and maturation of the epithelial cells in the normal bladder mucosa is accompanied by a decrease in CD44 protein expression. However, carcinoma cells overexpress standard and variant CD44 isoforms and continue to do so as they proceed through the thickened epithelial layer to the luminal surface and after they are shed into the urine. Conclusions —The abnormal expression of CD44 proteins in exfoliated cancer cells may be a useful marker for the noninvasive diagnosis of bladder cancer.